The artistic practice-research-teaching (ART) nexus: Translating the information flow - Bennett, Dawn; Wright, D.; Blom, D. (University of Wollongong, 2010)
This paper reports findings from interviews with fourteen Australian artist academics, who discuss the complex relationships between their Arts practice, their Research and their Teaching. We refer to this as the ART nexus because of the strong flow of information reported between these three activities. However, this information flow is not achieved without conflict. Conflict arises over the balance of time available and different mindsets required for differing activities, and there can be hesitation about analysing intuitive creative thought. The findings reveal ways in which information is ‘translated’ for different audiences including undergraduate and postgraduate students, who are both recipients of and contributors to the nexus. The article problematises the ART nexus in an attempt to offer greater insight into the ways in which individual artist academics teach through their arts practice and their research, within a university system that struggles to accommodate this breadth of endeavour.